Attribution of early deaths associated with atmospheric emissions of different economic sectors in Colombia in the year 2018 (2020)
"The National Institute of Health estimates that currently 15,681 premature deaths a year in Colombia are attributable to air pollution. However, little is known about the contribution of various economic sectors to the concentrations of air pollutants at the national and local level. In this project, we use a state-of-the-art chemical transport model to formulate a methodology to determine the sectoral contributions to the levels of air pollution in the country. The chemical transport and meteorological model, WRF-Chem V3.9, was implemented for a 3267 km by 3267 km domain in northern South America at horizontal resolution of 27 x 27 km, and with 41 vertical levels. In addition, two nested domains with a spatial resolution of 9 x 9, and 3 x 3 kilometers respectively were configured, with the highest resolution domain centered in the city of Bogotá. Anthropogenic emissions were taken from the EDGAR global emissions inventory V.4.3.1 (2010) and complemented with the local inventory of the Bogotá District Department of the Environment (2012). Emissions were disaggregated into 5 sectors: Agricultural, Electric Power Generation, Industrial, Land Transportation, Commercial and Residential and otherþs sectors. Seven scenarios were built to carry out the sectoral attribution: a base scenario which includes total emissions (i.e., including all sectors), and further 6 more scenarios in which emissions from a given economic sector were eliminated. This analysis establishes the attribution of each sector to the concentration of PM2.5, NOX, SOX, CO, and O3. The results obtained in this study show that the land transport sector is responsible for 329 premature deaths from cardiovascular and respiratory diseases associated with environmental contamination by PM2.5 and O3 in Colombia as of the simulation date, in addition 23% of these deaths occur in Bogotá..."